AN ANALYSIS OF SUBTITLING SLANG EXPRESSIONS AND READABILITY IN PURPLE HEART MOVIE FROM ENGLISH INTO INDONESIAN - Amalia Ayu Savitri; Sriyono (UIN Raden Mas Said Surakarta, 2023)
Subtitling strategies is part of translation process to gain a good result. The purpose of this study is to identify the slang expressions and analyze the subtitling strategies, slang types, and the readability rating of subtitle in Purple Heart movie. The data of this study is the subtitle text that contains slang expressions in Purple Heart movie. The data of this study is collected by searching and downloading, identifying, and classifying the data that contains slang expressions to the subtitling strategy and slang types. This study also uses a method with a questionnaire test on 11 respondents to determine the level of readability of the translation results. The writer analyzes the data using qualitative research according to Miles and Huberman's techniques, such as data reduction, data display, and conclusion. The result of this study shows that there are 73 data of slang expressions. The result of slang types shows that general slang with 44 data and specific slang with 29 data. The subtitling strategies applied in the data is only 5 strategy out of ten they are transfer with 34 data, paraphrase with 23 data, deletion with 9 data, condensation with 4 data, and expansion with 3 data. The result of the readability rating in the translation of slang expressions in the subtitle of Purple Heart movie shows that there are 803 data. The most dominant used is the readable category with 558 data, less readable with 173 data, and unreadable with 72 data.